Identification of Old Javanese Food in Serat Chentini Through Visual Storytelling (International Journal of Psychosocial Rehabilitation, 2020)
Food diversity owned by the community is one of Indonesia's cultural riches. For Javanese people, traditional food is not only food but also includes drinks. Geographical conditions and conditions of each region in Java are factors that cause differences in the types of food. Documentation about the richness of Javanese food is stored in one of Javanese literary works, which is Serat Chentini or often referred to as the Javanese Cultural Encyclopedia. Serat Chentini documents the basic ingredients of Javanese food which are the main food ingredients but are also served to entertain guests and complete traditional ceremonies. In addition to the types of Javanese food, in Serat Chentini also mentioned locations where these foods can be found. The combination of the appearance of Javanese food with the location of its food in the Java region can be documented into a Visual Storytelling about the traditional Javanese food footprint. The book titled Milang Warisan can be used as a knowledge of the distribution of Old Javanese food which has become the starting point for the development of traditional Javanese cuisine until today.